The humans [videorecording (DVD)] - Jenkins, Richard, 1947-; Houdyshell, Jayne, 1953-; Schumer, Amy; Feldstein, Beanie; Yeun, Steven; Squibb, June, 1929-; Karam, Stephen (Lionsgate, 2022)
Erik Blake has gathered three generations of his Pennsylvania family to celebrate Thanksgiving at his daughter's apartment in lower Manhattan. As darkness falls outside and eerie things start to go bump in the night, the group's deepest fears are laid bare. The piercingly funny and haunting debut film from writer-director Stephen Karam, adapted from his Tony Awardʼ-winning play, THE HUMANS explores the hidden dread of a family and the love that binds them together.